2021
DOI: 10.1155/2021/6692695
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Gestational Diabetes Mellitus: A Meta-Analysis

Abstract: Gestational diabetes mellitus (GDM) is a major public health issue, and the aim of the present study was to identify the factors associated with GDM. Databases were searched for observational studies until August 20, 2020. Pooled odds ratios (ORs) were calculated using fixed- or random-effects models. 103 studies involving 1,826,454 pregnant women were identified. Results indicated that maternal   age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 38 publications
0
34
0
1
Order By: Relevance
“…Previous studies reported that being overweight or obese pre-pregnancy, non-primipara, lack of physical activity, and carrying a baby boy were risk factors for GDM. In stratified analyses of this study, the positive associations between Mn levels and GDM remained significant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that being overweight or obese pre-pregnancy, non-primipara, lack of physical activity, and carrying a baby boy were risk factors for GDM. In stratified analyses of this study, the positive associations between Mn levels and GDM remained significant.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of GDM in the Indian population is high compared with other Asian countries [7,16,19,20] . This evidence indicates that the prevalence of GDM might also be affected not only by different screening methods and diagnostic criteria but also by the characteristics of the population [6][7][8][9][10]14] . In the present study, 7.6% pregnant women (46) were diagnosed as GDM using DIPSI recommended 75 gm OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…Although maternal age is an established risk factor for gestational diabetes, the exact cause of the association between maternal age and GDM is not clearly understood. The association of advanced maternal age with higher parity, obesity, and increased insulin resistance due to parity, higher levels of circulating adipokines and inflammatory markers, as well as oxidative stress may partially clarify this association [3,13,14,20,29] . Similarly, the educational status of pregnant women was found to be significantly associated with the prevalence of gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that a key factor in limiting the action of insulin is the increased inflammatory response associated with excess body fat [ 62 , 63 , 64 ]. The risk factors for GDM are pre-pregnancy obesity and excess weight, EGWG, a family history of T2DM, advanced maternal age, multiparity, GDM during previous pregnancies, giving birth to a baby with a birth weight greater than 4000 g in previous pregnancies, and polycystic ovary syndrome [ 65 , 66 ]. It should be noted that diabetes often coexists with obesity.…”
Section: Pregnancy As a Window For The Development Of Metabolic Diseasesmentioning
confidence: 99%